Acceptance or refusal of convenience food in present-day prison. (1st November 2015) - Vanhouche, An-Sofie
Highlights: We examine the introduction of ready-made meals in prison. Ready-made meals facilitate the organization of prison life. Prisoners highlight mainly negative attitudes toward convenience food. Abstract: Food in prison is an insufficiently researched topic. However, prisoners often highlight problems with and criticism of their prison meals. This article aims to further develop this topic by giving closer insight into the use and attitudes toward ready-made meals in the Tilburg prison. In this prison, prisoners receive ready-made meals. This is in contrast to Belgian prisons, from which they were transferred, where meals were made from scratch. This change in the food system led to commotion and complaints. To understand the situation, interviews with prisoners and staff were conducted and observations in the Tilburg prison were made. The results showed that a food system can have considerable influence on prison experiences. In addition, and contrary to what earlier reports have mentioned, the ready-made meals also have some advantages, especially for the organization of daily prison life. However, most prisoners had negative attitudes toward these meals.